v.1 - Khalakdina, Margaret (New Delhi, 2008)
A contextual complement to its prequel, this volume presents the major socio-psychological and cultural influences on the development of an Indian. This volume analyzes development of person from childhood to adolescence in the Indian context. The author incorporates psychological, sociological, anthropological, and even economic and socio-political dimensions that affect development, giving the work multi-disciplinary breadth. While most books on the subject are based on Western patterns and examples, which are vastly different from the Indian setting, this book is context-specific and content-sensitive to the Indian psyche. It culminates its discussions with identifying the future foci that could give empirical information for creating a theoretical base on the development of the Indian.
Keywords: India-Social conditions